Establishing reference values for tensiomyography-derived parameters in soccer players: insights from a systematic review, meta-analysis and meta-regression - Paravlic, A. H. (Biology of Sport, 2025)
This systematic literature review (SLR) aimed to comprehensively synthesize existing studies that have reported on TMG-derived parameters of lower extremities in soccer players. The PubMed, Web of Science, and EBSCOHost (including MEDLINE, SPORTDiscuss, ERIC, DOAJ, and SCOPUS) databases were searched from inception to the 31st of August, 2023. Reports were eligible if they satisfied the following criteria: recruited active soccer players, with no restriction on race, sex, age, level of expertise, or health status; studies utilizing TMG for measuring muscle contractile properties. In total, 25 published journal articles from 22 original studies were included in the current review, encompassing a total of 1224 participants (4% females). The analysis considered various muscles, with the biceps femoris (BF), rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), semitendinosus (ST), gastrocnemius lateralis (GL), and gastrocnemius medialis (GM) being investigated. Significant variations were observed in TMG parameters across different muscles, age categories, and levels of play. The quality of evidence varied from low to moderate for all analyses. The meta-regression analysis indicated that age moderated several TMG-derived parameters in lower limb muscles including BF Vc, RF Td and Vc, ST Dm and sustain time, VL Dm, Tc, Td and relaxation time (Tr), and VM Tc, Td and Tr, respectively. In conclusion, the current review illuminated the multifaceted applications of TMG in assessing lower extremity muscles in soccer players. Beyond evaluating muscle contractile properties in various superficial muscles of the lower limbs in soccer players, TMG-derived parameters may serve as potentially valuable markers in identifying neuromuscular risk factors for anterior cruciate ligament injuries and predicting hamstring-related injuries.